2018
DOI: 10.1364/oe.26.007866
|View full text |Cite
|
Sign up to set email alerts
|

Generating a three-dimensional hollow spot with sub-diffraction transverse size by a focused cylindrical vector wave

Abstract: A three-dimensional (3D) hollow spot is of great interest for a wide variety of applications such as microscopy, lithography, data storage, optical manipulation, and optical manufacturing. Based on conventional high-numerical-aperture objective lenses, various methods have been proposed for the generation of 3D hollow spots for different polarizations. However, conventional optics are bulky, costly, and difficult to integrate. More importantly, they are diffraction-limited in nature. Owing to their unique prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…[ 7,8 ] Based on the concept of superoscillation, [ 9–11 ] a variety of sub‐diffraction or super‐resolution optical devices have been demonstrated either theoretically or experimentally, including scalar super‐resolution metalenses [ 12–22 ] and vector super‐resolution metalenses. [ 23–33 ] Such super‐resolution devices have been successfully shown great potential in label‐free super‐resolution microscopy [ 13,21,34,35 ] and super‐resolution telescope. [ 36 ] However, most previously reported super‐resolution metalenses only work at one single wavelength [ 37 ] or several designed discrete wavelengths, [ 38,39 ] while broadband achromatic metalenses working in the visible [ 40–42 ] and near‐infrared spectrum [ 43–46 ] as well as THz regime [ 47 ] are restricted by the Abbe DL.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] Based on the concept of superoscillation, [ 9–11 ] a variety of sub‐diffraction or super‐resolution optical devices have been demonstrated either theoretically or experimentally, including scalar super‐resolution metalenses [ 12–22 ] and vector super‐resolution metalenses. [ 23–33 ] Such super‐resolution devices have been successfully shown great potential in label‐free super‐resolution microscopy [ 13,21,34,35 ] and super‐resolution telescope. [ 36 ] However, most previously reported super‐resolution metalenses only work at one single wavelength [ 37 ] or several designed discrete wavelengths, [ 38,39 ] while broadband achromatic metalenses working in the visible [ 40–42 ] and near‐infrared spectrum [ 43–46 ] as well as THz regime [ 47 ] are restricted by the Abbe DL.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, various types of superoscillatory lenses have been demonstrated, including linear‐focusing lenses, [ 18,19 ] spot‐focusing lenses, [ 20,21 ] long‐depth‐of‐focusing lenses, [ 22–24 ] and vector wave superoscillatory lenses. [ 25–30 ] So far, the smallest PSF that has ever been experimentally demonstrated has a full‐width‐at‐half‐maximum (FWHM) value of 0.33λ, [ 31 ] where λ is the working wavelength. Due to their comparative large sidelobes, those super‐resolution lenses are not suitable for direct imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Both theoretical and experimental results have indicated that this optical lever results in significant attenuation of the longitudinal component in the image field 64 . The absence of longitudinal polarization was verified in later experimental investigations of focused superoscillation optical fields 139,161 , which showed clear deviations of image fields from the theoretically predicted electric fields and satisfactory agreement was observed between the image fields and the transverse components that were obtained via numerical simulation.
Fig. 11Superoscillation optical field characterization systems. a The superoscillatory fields are obtained by a high-NA microscope with an objective lens mounted on a 1D nanopositioner (1D NP), where the camera is used to obtain the 2D intensity distribution of the diffraction pattern.
…”
Section: Characterization Of Superoscillatory Optical Fieldsmentioning
confidence: 74%
“…11b, to measure the longitudinal electric components, the fibre tip axis must be set perpendicular to the polarization direction or at an angle at which the tip can respond to the longitudinal polarization to a certain extent 88,130 . A titled tip can be used to map the entire electric field within the plane of a tilted nanofibre with satisfactory similarity to the theoretical result of the entire field 130,139 , and the distortion that is caused by the polarization selectivity can be minimized with a tilt angle of 45°.…”
Section: Characterization Of Superoscillatory Optical Fieldsmentioning
confidence: 76%
See 1 more Smart Citation